Lyapunov function of SIR and SEIR model for transmission of dengue fever disease. (1st January 2013) - Syafruddin, S.; Noorani, Mohd Salmi Md.
In this paper, we construct a new Lyapunov function for a variety of SIR and SEIR model in epidemiology. Lyapunov functions are used to show that when the basic reproduction ratio is less than or equal to one, the disease-free equilibrium is globally asymptotically stable and the basic reproduction ratio is greater than one, and the endemic equilibrium is also globally asymptotically stable for both models.